Management Communication with impact! - Lundholt, Marianne Wolff (Language at Work - Bridging Theory and Practice, 2010)
“To be effective in business, you have to communicate well. To be a good manager, you have to communicate exceptionally well”. This was the opening of a newsletter sent to all people managers in Danfoss on October 13, 2010 from Chief Reputation Officer Ole Daugbjerg. Attached was a booklet titled `Management Communication Tool Kit´.